Corporate Criminal Accountability in Indonesia and Other Countries - Rr. Dijan Widijowati (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
Corporations are established with different objectives and ways to achieve different goals, not only in ways that are permitted by law but also in ways that are prohibited by law. Today, corporations are frequently involved in various criminal acts or used as a means to commit criminal acts. Therefore, it is a fact that cannot be denied that the role of corporations is currently very important in people's lives. Corporations as perpetrators of criminal acts in terms of criminal liability need to be considered carefully. Because today's corporations are increasingly playing an important role in people's lives, especially in the economic sector, Business activities, or the business world in general, are the main basis for meeting the competitive needs of life. In the United States and the United Kingdom, they also regulate corporate criminal liability, so the problem that can be formulated is how corporate criminal responsibility is regulated in Indonesia, the United States, and the United Kingdom. The research was carried out using a normative-juridical method using secondary data that was used as research material. The results of the study show that corporate criminal responsibility in Indonesia and other countries has agreements and differences, both in terms of regulation and the application of sanctions